Low-Level Laser and TENS Therapy Assessment for the Treatment of Temporomandibular Joint Disorder - Silpiranjan Mishra; Atul Anand Bajoria; NC Sangamesh; Ajit Kumar Swain; Sanjay Kumar Sahoo; Abinash Mohapatra (Journal of Pharmacy and Bioallied Sciences)
Introduction: The most prevalent conditions in the population are temporomandibular disorders (TMDs), which are linked to a number of morbidities. A number of treatment options have been proposed, and some of the most successful ones include low-level laser therapy (LLLT) and transcutaneous electrical nerve stimulation (TENS) therapy. Objectives: The purpose of this study was to examine the effectiveness of two therapies—TENS treatment and LLLT—in the management of morbidities related to temporomandibular joint (TMJ) disorders. Materials and Methods: Based on inclusion and exclusion criteria, a total of 50 patients who had been sent to the oral medicine outpatient department and had been pre-diagnosed with TMJ disorders were randomly assigned to two groups, with 25 patients in each: Group I received TENS therapy, while Group II received LLLT. The acquired data was assessed statistically. Result: Both groups showed a substantial decrease in discomfort, an increase in mouth opening, and a decrease in muscular tenderness when compared to within groups. LLT was more effective than TENS for TMD treatment. Conclusion: While TENS and LLLT both had good results, LLLT appeared to outperform TENS therapy in terms of muscle tenderness factors.